2020
DOI: 10.7717/peerj.10639
|View full text |Cite
|
Sign up to set email alerts
|

Improved plaque assay for human coronaviruses 229E and OC43

Abstract: In light of the COVID-19 pandemic, studies that work to understand SARS-CoV-2 are urgently needed. In turn, the less severe human coronaviruses such as HCoV-229E and OC43 are drawing newfound attention. These less severe coronaviruses can be used as a model to facilitate our understanding of the host immune response to coronavirus infection. SARS-CoV-2 must be handled under biosafety level 3 (BSL-3) conditions. Therefore, HCoV-229E and OC43, which can be handled at BSL-2 provide an alternative to SARS-CoV-2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 30 publications
2
35
1
Order By: Relevance
“…In contrast, HCoV-OC43 produced CPE (cell lysis, cell rounding and vacuolization) in MRC-5 cells starting on day 2 which continued through day 7. Also, contrary to some previous reports (Bracci et al 2020; Hirose et al 2021), CPE was observed in HCoV-OC43 infected Vero E6 cells. Cell rounding and lysis began on day 3 and continued until day 7 (Fig.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, HCoV-OC43 produced CPE (cell lysis, cell rounding and vacuolization) in MRC-5 cells starting on day 2 which continued through day 7. Also, contrary to some previous reports (Bracci et al 2020; Hirose et al 2021), CPE was observed in HCoV-OC43 infected Vero E6 cells. Cell rounding and lysis began on day 3 and continued until day 7 (Fig.…”
contrasting
confidence: 99%
“…“the common cold,” and are typically restricted to the upper respiratory tract. Also, a review of extant literature finds researchers using a variety of methods to quantify HCoV-OC43 employing different cell lines, HRT-18 (human colon cancer cells) (Lambert et al, 2008), RD (human rhabdosarcoma cells) (Schmidt, Cooney, and Kenny, 1979), MRC-5 (human lung fibroblasts) (Collins, 1993; Collins, 1995; Kim et al, 2019), BSC-1(African green monkey kidney cells) (Bruckova et al, 1970), Vero E6 expressing TMPRSS2 (Hirose et al, 2021) and Mv1Lu (mink lung cells) (Bracci et al, 2020), using different titration assay types (either TCID 50 or plaque assay), the latter with different types (agarose, Avicel, methylcellulose) and percentages of overlays, employing different incubation temperatures (33°C or 37°C), times (2-7 days) and detection methods (immunoperoxidase with chromagen, immunofluorescence, neutral red, crystal violet). This lack of standardization hampers evaluation and comparison of study results, as the different cell lines may have different growth kinetics and susceptibilities to virus grown in heterologous cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TCID 50 values were calculated by the Spearman & Kärber algorithm as previously described. 48 OC43 plaque assay was carried out on RD cells as described by Bracci et al ( 49 )…”
Section: Methodsmentioning
confidence: 99%